Enhancing Mechanical Characteristics of 6061-T6 with 5083-H111 Aluminum Alloy Dissimilar Weldments: A New Pin Tool Design for Friction Stir Welding (FSW) - Khalafe, Wazir Hassan; Sheng, Ewe Lay; Isa, Mohd Rashdan; Shamsudin, Shazarel (Mdpi, 2024)
This research addresses the escalating need for lightweight materials, such as aluminum and magnesium alloys, in the aerospace and automotive sectors. The study explores friction stir welding (FSW), a cost-efficient process known for producing high-quality joints in these materials. The experiment involved the welding of dissimilar aluminum alloys (AA5086-H111 to AA6061-T6) using a novel pin tool design with welding parameters such as holding time, pin tool length, tool spindle speed, and linear speed fine-tuned through a design of experiment (DOE) approach. A comparative analysis of two tool designs revealed that the newly introduced design substantially improved mechanical properties, particularly tensile strengths, by 18.2% relative to its predecessor. It is noteworthy that FSW joint efficiency is 83% when using a normal tool design in comparison with 92.2% when using a new tool design at similar FSW parameters. The new tool achieved the parameter values leading to the maximum tensile strength of 317 MPa with 3 mm thickness (Th), 25 s holding time (Tt), 0.1 mm dimension (L), 1600 rpm spindle speed (SS), and 30 mm/min feed velocity (Fr). In comparison, the normal tool achieved a maximum UTS of 285 MPa, 5 mm Th, 25 s Tt, 0.3 mm L, 800 rpm SS, and 90 mm/min Fr. The new tool design, with longitudinal and circular grooves, improves heat input for plastic deformation and alloy mixing during welding. Subsequent analysis of the joint’s microstructure and microhardness shows its similarity to the original alloys.